Metatheory and Diplomatics: building a new model of analysis for the identification of archival records - Tognoli, Natalia Bolfarini [UNESP] (Univ Zaragoza, 2015)
Since the 1980s Archival Science has faced new challenges regarding the organization of archival knowledge. In this way the concept of identification emerged as part of the record management processes. This process counts with the studies of contemporary diplomatics, once it aims to understand the records creation processes from the document analysis offered by the diplomatic method. This paper aims to present a new model for records identification, based on the diplomatic methods developed in 17th, 19th and XX centuries. Therefore, it counts with metatheory as a methodology for knowing and analyzing the diplomatic methods. The results show a strong methodological support of metatheory to the studies of Knowledge organization, as well as a strong support of Diplomatics to the archival studies.
Keywords: Diplomatics; Metatheory; Document identification; Archival science; Archival records